2020
DOI: 10.3390/app10248860
|View full text |Cite
|
Sign up to set email alerts
|

Energy Balance, Cost and Architectural Design Features of 24 Building Integrated Photovoltaic Projects Using a Modelling Approach

Abstract: This paper presents the energy balance, architectural design features and cost aspects of 24 building integrated photovoltaic (BIPV) projects in three different contexts, namely BIPV in residential, office and historical buildings. These BIPV projects have been modelled and evaluated for different geographic locations because the European Energy Performance of Buildings Directive (2018/844/EU) has resulted in country-specific regulations and situations aimed towards the reduction in energy consumption, and hen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Studies have confirmed that the electricity provided by BIPV can reduce a considerable amount of CO 2 per year [36]. BIPV systems could be used in different contexts and building types [37]. However, if the low-carbon design of the BIPV cannot be realised, the contribution of BIPV to carbon emission reduction will be significantly reduced.…”
Section: Definition Of Bipv From the Perspective Of Architectural Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have confirmed that the electricity provided by BIPV can reduce a considerable amount of CO 2 per year [36]. BIPV systems could be used in different contexts and building types [37]. However, if the low-carbon design of the BIPV cannot be realised, the contribution of BIPV to carbon emission reduction will be significantly reduced.…”
Section: Definition Of Bipv From the Perspective Of Architectural Designmentioning
confidence: 99%
“…Integration of PV technology and other renewable energy technolo an important role in providing a long-term energy supply with little emissions [34 over, there is a growing consensus that BIPV systems will be the backbone of t energy building (ZEB) European target by 2020 [35]. Studies have confirmed that tricity provided by BIPV can reduce a considerable amount of CO2 per year [3 systems could be used in different contexts and building types [37]. However, if carbon design of the BIPV cannot be realised, the contribution of BIPV to carbon e reduction will be significantly reduced.…”
Section: Definition Of Bipv From the Perspective Of Architectural Designmentioning
confidence: 99%
“…Risks associated with the development of BIPV residential projects have been studied across multiple levels: user acceptance [11,24,25], market development potential [26,27], economic benefit [27,28], environmental benefit [29], and technical barriers [30,31]. To encourage BIPV residential projects in the community, it is necessary to consider public acceptance of BIPV technology [24].…”
Section: A Study Of Development Risks In Bipv Residential Projectsmentioning
confidence: 99%
“…Other interesting tools based on engineering criteria address the conceptual phase of the design, allowing the control of the evolutionary progress through the interactive selection of parent solutions by mean of parametric modelling, performance simulation software, genetic algorithms and an online database, concluding about the key role played by geometry in architecture in relation to performance-oriented design [14]. Other researches use interesting methodologies to evaluate the performance of various types of projects in different locations in Europe [15], but due to the large geographical scope and variation of solar irradiation, there is not a similar performance and specific conclusion about solar incidence results. Some engineering schools are committed to develop tools for student engineering explorations through modelling and simulations with the use of CAD, developing advanced solar schemes for single-family homes [16], without consider multifamily buildings due to their complexity.…”
Section: Measurements In Pv Students' Projectsmentioning
confidence: 99%